4a+3b can not be algebraically simplified. It can be evaluated if you assign values to a and b.
11a+7b-(3b-2a)
8b -2a
11a+11b
3a - 2b
4a + 3c - 2b - c + a - b = 5a - 3b + 2c
3(4a+b+2c)
The equation cannot be solved as there are two unknowns. However it can be simplified and the two unknowns (a and b) expressed in terms of the second unknown. 1) Expressing a in terms of b 4a + 2 = 3b - 5 4a = 3b -7 if desired this could be stated as a = (3b - 7)/4 2) Expressing b in terms of a 3b - 5 = 4a + 2 3b = 4a + 7 if desired this could be stated as b = (4a + 7)/3
(4a - 3b)(4a + 3b)
2 x (2a + 3b - 6)
It can't be an equation, there is no sign of equality.
Think of 2 apples + 3 bananas + 4 apples.What can be added together?6 apples + 3 bananas6a+3b
Well, darling, to simplify 4a times 3b, you just multiply the numbers together to get 12, and then slap those variables together to get 12ab. It's as easy as making a martini on a Sunday afternoon. Cheers!